Pengaruh Budaya Korporat terhadap Kinerja Karyawan (Studi Pada PT. Bank Pembangunan Daerah Kalimantan Selatan Kantor Cabang Utama Banjarmasin) - Ahmad Mardian Umar; Saladin Ghalib; Taharuddin Taharuddin (JURNAL BISNIS DAN PEMBANGUNAN, 2014)
This research is focussing on knowing the influence of corporate culture such as service excellent, enthusiasm, prudence, professional, integrity and team work (thiese six variables called independent variables) to the employee performance (as dependent variable) in PT. Bank Pembangunan Daerah Kalimantan Selatan Main Branch Banjarmasin.The research uses a quantitative approach by using 100 employees of PT. Bank Pembangunan Daerah Kalimantan Selatan Main Branch Banjarmasin as samples. Measurement variables by using a Likert scale with a score of 1 to 5 scale. Data analysis using statistical techniques and a multiple linear regression to test the significant level using a t test with SPSSThe result of this research show as that all variables of corporate culture such as service excellent, enthusiasm, prudence, professional, integrity and team work partially has significant and positive influence to the employee performance. The greatest influence or dominan variable is a professional with regression coefficients is 0.338 or 33.8% to the variable employee performance compared with the other five indenpendent variables.Keywords: Service Excellent, Enthusiasm, Prudence, Professional, Integrity, Teamwork, Employee Performance